Treatment of Source-Separated Human Feces via Lactic Acid Fermentation Combined with Thermophilic Composting. Issue 4 (2nd October 2017) - Andreev, N.; Ronteltap, M.; Boincean, B.; Lens, P. N. L.
ABSTRACT: Human feces from urine diverting dry toilets can serve as valuable soil conditioners. For a successful agricultural application, an efficient pathogen reduction needs to be ensured, with no negative effects on plants. This study assessed the efficiency of lacto-fermentation combined with thermophilic composting on pathogen removal from human feces and the post-treatment effects on germination and growth of radish ( Raphanus sativus ) and tomatoes ( Lycopersicum esculentum ) compared to lacto-fermentation combined with vermi-composting and the control. The NH4 + -N/NO3 − -N ratio of 3.0 and 3.6, respectively, suggested the obtained compost and vermi-compost was not yet mature. A complete reduction in the concentration of all investigated bacterial indicators (i.e., coliforms, Escherichia coli, Enterococcus faecalis, and Clostridium perfringens ) from 5–7 log CFU g −1 to below detection limit (<3 log CFU g −1 ) was achieved after lacto-fermentation combined with thermophilic composting. Lacto-fermentation combined with vermi-composting also contributed to pathogen die-off, but coliform bacteria were reduced to only 5 log CFU g −1 . Fertilization of seeds of radish by compost obtained after lacto-fermentation combined with thermophilic composting led to a higher germination index than by the vermicast obtained by lacto-fermentation and vermi-composting (90% versus 84%). Moreover, significantly bigger average fruit weight and total biomass per tomato plant ( p < 0.05) were obtained after compost amendment compared to vermicast or the control.